The Effect of Teacher Competency on the 2021 Elementary School National Assessment Result - Amelia Wahyu Puspitaningtyas; Thia Jasmina (Borong Newinera Publisher, 2023)
Education aims to develop students' potential and competencies as measured by the National Assessment (AN) as the latest standardized test organized by the Ministry of Education, Culture and Research. The AN results are contained in the Education Report Card platform. In the education system, teachers play a crucial role in ensuring that the learning process is optimized. Therefore, knowledge of the influence of teacher competence on student competence can help improve the overall quality of education. This study aims to provide empirical evidence regarding the relationship between teacher competence and AN outcomes at the primary school level in 2021. The method used is logistic regression with the dependent variable being student literacy and numeracy competency achievement at the district/city level. The independent variables of this study consist of teacher competency as the main independent variable described by the percentage of certified teachers, while the control independent variables consist of teacher characteristics, school characteristics, socio-economic characteristics, and regional characteristics. The results of this study show that there is no significant relationship between teacher competencies and students' literacy and numeracy competencies. The control variables that were significant for literacy competencies consisted of student-teacher ratio, school accreditation, school internet access, life expectancy, and district geographical location, while in numeracy competencies only the variables of electricity and school internet access, as well as life expectancy and per capita expenditure were significant.